Pregnancy with cardiac disease: a retrospective five year study in a teaching hospital - Rangaswamy, Manohar; Ramachandra, Pradeep Musale (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prevalence of heart disease in pregnancy is found to vary between 0.3%-3.5%. Heart disease is one of the 3 major indirect causes of maternal mortality in India. Methods: This is a retrospective study conducted in department of OBG, Mandya Institute of Medical Science, India. Mandya for a period of five years from January 2011 to December 2015.All cases of cardiac disease during pregnancy admitted during this period will be included in the study. All case records will be obtained from medical record section and carefully analysed to find out the incidence, various types of cardiac diseases, its relation with respect to duration of pregnancy and its outcome in relation to mode of delivery, birth weight, maternal and perinatal morbidity. Results: Cardiac disease was more commonly present among Primigravida (53.8%) which correlates with the study conducted Mahesh et al (52.7%). Rheumatic heart disease (RHD) was the commonest cardiac lesion, which was also found to be the major form of heart disease in various studies. Mitral stenosis (38.6%) is the most common RHD .65.3% (34 cases) was delivered by vaginal route and 34.6% (18 cases) were delivered by LSCS. Conclusions: Thus good antenatal care including more frequent antenatal check-up, educating the patient regarding the various complications and taking the physician help during antepartum or intrapartum or postpartum period will definitely reduce the maternal complications associated with it.